"Cry Clubs for Prentices": (Not) Performing Riot in Thomas Dekker's The Shoemaker's Holiday. (3rd July 2018) - Williamson, Matt
ABSTRACT: This article situates Thomas Dekker's The Shoemaker's Holiday (1599) in the context of the London riots of 1595. By contrast with the more overtly festive Shrove Tuesday riots of the Jacobean period, this late sixteenth-century uprising constituted an overt threat to authority. Attention to this context provides a means of understanding the complex mixture of disorder and festivity which characterises Dekker's play. The article emphasises the text's complex temporality, arguing that it presents an idealised image not of contemporary London, but rather of its historical past. Through its representation of the livery company system and its structures of hospitality, the play offers an alternative to the socio-economic conflicts which defined early modern London. But these images of London's past are consistently situated in opposition to elements of tension rooted in the contemporary present. The result is a politics of nostalgia, which deploys the spectre of riot as a means to assert the necessity of a rejuvenated livery company system.